Expanding Public Participation in Science Practices Beyond Data Collection. (13th April 2021) - Hinojosa, Leighanna; Riedy, Robbin; Polman, Joseph; Swanson, Rebecca; Nuessle, Tiffany; Garneau, Nicole
This study was conducted in a museum-based lab setting where scientists research the genetics of taste. Unlike academic labs with graduate students, the museum lab model trains volunteers (community scientists) who are (in true citizen science fashion) primarily responsible for enrolling museum guests into clinical studies; thus, they collect the bulk of the data for the research. Like most public participation in science research, the non-professional contributions have historically been largely limited to data collection; however, this study shows the power of invitations and structured opportunities for expanded participation among citizen scientists in a wider range of science practices. Through interpretive case study research, we examine how community scientists exercise agency and respond to opportunities for expanded participation in scientific practices including study design, data analysis, and dissemination of scientific findings through work on scientific articles. The case study research findings show that providing opportunities for involvement is only part of what accounts for community scientists' expanded participation. Dialogic negotiation of participation is also necessary, through bids and responses to bids, and through proffered guidance and scaffolding. Committed involvement thus entails deep cultivation and nurturing by both the museum staff, and at times, other more knowledgeable volunteers. Expanded participation is also bolstered by one's capacity, motives for, and satisfactions from pursuing those opportunities that align with past, present, or future interests and identifications. Such interests and identifications contribute to community scientists' willingness to overcome barriers and time constraints when they arise.